37.1k views
21 votes
Please help me with the correct answer

Please help me with the correct answer-example-1
User Leovp
by
4.8k points

2 Answers

9 votes

Answer:

y=2(-2)+3

y=-1

y=2(-1)+3

y=1

y=2(0)+3

y=3

y=5

y=7

User Alex Robinson
by
5.4k points
11 votes

Answer:

(From left to right)

1st y (output): -1

2nd y (output): 1

3rd y (output): 3

4th y (output): 5

5th y (output): 7

Explanation:

Substitute each x (input) into the given equation and solve. For example, to get the first y (output), substitute "-2" into the "x" in the equation, giving you "y = 2(-2) +3", then solve it.

Multiply 2(-2) to get -4, then add 3 to get -1.

User Normajean
by
4.8k points